Catalyzing sustainable development: insights from the international workshop on STI policies and innovation systems in Central America - Jorge A. Huete-Pérez; Alma Cristal Hernández-Mondragón; Douglas S. Massey; Luz M. Cumba García; Bernard Amadei; Nadia De León Sautú; Maria L. Acosta; Maria L. Acosta; Omar Asensio; Omar Asensio; John Boright; Serena Cosgrove; et al. (Frontiers in Research Metrics and Analytics)
This article examines the landscape of Science, Technology, and Innovation policies in Central America, focusing on Nicaragua, Guatemala, Honduras, and El Salvador. These nations face significant challenges in leveraging STI for sustainable development, including financial constraints and limited resources. Additionally, Central America struggles with systemic issues such as corruption, violence, and high levels of emigration, further complicating efforts to advance STI. A workshop organized by Georgetown University's Science Technology and International Affairs program brought together scholars to discuss STI policies, resulting in key recommendations. The article highlights critical challenges, including over-reliance on state funding, stagnant researcher numbers, and the pressing need for research diversification. It emphasizes the importance of youth engagement, leadership, and resilience in shaping effective STI policies. Recommendations include investing in science education, establishing governmental scientific advisory bodies, promoting research diversity, and addressing climate change through STI strategies. The findings provide valuable insights for scholars, policymakers, and international organizations working with less developed nations globally.